Diagnosis and treatment of pulmonary embolism during the COVID-19 pandemic: A position paper from the national pert consortium (2020)
The co-existence of COVID-19 and PE, two life threatening illnesses, in the same patient presents a unique challenge. Recent guidelines have delineated how best to diagnose and manage patients with PE. However, the unique aspects of this virus confound both the diagnosis and treatment of PE, and thus require modification of established algorithms.1- 6 Important considerations include adjustment of diagnostic modalities, incorporation of the pro-thrombotic contribution of COVID-19, management of two critical cardio-respiratory illnesses in the same patient, and protecting patients and health care workers while providing optimal care. The benefits of a team-based approach for decision-making and coordination of care, such as that offered by pulmonary embolism response teams (PERT), has become more evident in this crisis. The importance of careful followup care also is underscored for patients with these two diseases with long-term effects. This position paper from the PERT Consortium specifically addresses issues related to the diagnosis and management of PE in the COVID-19 patient.